Knitting, Weaving, Embroidery, and Quilting as Subversive Aesthetic Strategies: On Feminist Interventions in Art, Fashion, and Philosophy - Natalia Anna Michna (ZoneModa Journal, 2020)
In the paper I pose the question of how, on artistic, aesthetic, and philosophical levels, decoration and domestic handicrafts as subversive strategies enable the undermining and breakdown of class-based and patriarchal divisions into high and low, objective and subjective, public and private, masculine and feminine. I explore whether handicrafts, in accordance with feminist postulates, are transgressive, transformative, and inclusive. I link handicrafts with the feminist perspective, since, in the second half of the twentieth century, it was precisely the feminist movement that initiated significant changes in the social and cultural perception of women, femininity, and gender relations. Thus I apply this perspective in the first place to the analysis of selected works of contemporary art in which handicrafts is used not only as a means of artistic expression, but also as a subversive aesthetic strategy. I also demonstrate how the world of fashion transforms and aesthetizes handicrafts, whose presence in fashion makes it an area in which, in addition to imperatives and aesthetic values, social attitudes, ethical values, and world views are shaped. Finally, referring to the works of selected feminist authors (Mary Field Belenky, Mary Daly, Evelyn Fox-Keller, Donna Haraway), I show how these researchers have metaphorically interpreted handicrafts as specifically feminine ways of creating and developing knowledge.